Analysis of The Effectiveness of Hotel Tax, Restaurant Tax, and Street Lighting Tax in Increasing Regional Tax Revenue of East Lombok Regency in 2018-2022 - Osalan, Lalu Ami; Alwi, Muhammad; Agustiana, Eka (Eastasouth Institute, 2024)
This study aims to analyze the effectiveness and contribution of hotel tax, restaurant tax, and street lighting tax in East Lombok Regency in 2018-2022. This study uses a quantitative research type. Data obtained from the Regional Revenue Agency of East Lombok Regency in 2023. The results of this study indicate that the effectiveness of hotel tax in 2018-2022 obtained an average of 42.44%, which falls into the ineffective criteria, the effectiveness of restaurant tax obtained an average of 99.87%, which falls into the effective criteria, and the effectiveness of street lighting tax obtained an average of 98.95%, which falls into the effective criteria, while the hotel tax contribution obtained an average of 0.95%, which falls into the very poor criteria, the restaurant tax contribution obtained an average of 7.35%, which falls into the very poor criteria, and the street lighting tax contribution obtained an average of 41.10%, which falls into the good criteria. The implications of this study explain that strict supervision of taxpayers should be carried out and re-registering taxpayers to ensure that all taxpayers have been registered and fulfill their tax obligations in order to significantly increase regional tax revenues.